The oldest occurrence of Crocodylus in Madagascar and the Holocene crocodylian turnover. Issue 6 (2nd November 2021) - Martin, Jeremy E.; Richardin, Pascale; Perrichon, Gwendal; Pochat-Cottilloux, Yohan; Phouybanhdyt, Brian; Salaviale, Celine; Adrien, Jerome
ABSTRACT: The island of Madagascar is home to a distinctive fauna and flora whose biogeographic history is not fully understood. Today's crocodylian population consists of a single species, the Nile crocodile, Crocodylus niloticus, whose colonization of the island may be very recent. In Madagascar, the genus Crocodylus has so far been described from a single subfossil specimen dated at 385 years cal BP, offering limited perspectives for discussing the timing of its arrival. On the other hand, another crocodyline, the now-extinct endemic Voay robustus, has been reported from several late Holocene localities throughout the island. Because of the earlier age of Voay robustus, it has been suggested that Crocodylus followed the extinction of this endemic species. Here, we report on a significantly older occurrence of the genus Crocodylus, between 7670 and 7510 years cal BP. The taxonomic identity of crocodylian subfossil specimens throughout Madagascar should be reevaluated in the context of this new occurrence, which could alter hypotheses of crocodylian turnover and the potential human impacts on the island.